LED Blink/Fade with Node MCU (International Journal of Innovative Research in Computer Science & Technology, 2021)
We all are living in the modern era of  science and technology. Things are changing day by day,  everything is becoming automatic and robotic day by day  life goes on LED’s (light emitting diodes). In this paper we  discussed the LED blink using node MCU and that Server  is an open software platform that runs on the ESP8266 that  allows things to be connected and messages to be  transferred using the Wi-Fi network. Furthermore, it may  solve most of those developer's demands on its own by  supplying many of the most application points of  embedded devices such as GPIO(general purpose input  /output), PWM (pulse width modulation) and so  on.Internet of things (IoT) refers to the tangible items some  of which are networked, processor speed, algorithms, and  some other techniques, and this also interface to something  and transfer information between computers and  applications well over World wide web.Because of  confluence of network technologies, such as cognitive  computing, affordable sensors, more popular internet of  things IoT, and advanced analytics, the area has  progressed. In this paper we are blinking the LED with the  help of a node MCU that is further connected to Wi-Fi and  IoT. The future scope of this study is LED light output will  continue to improve in the future, allowing mass–market  general illumination applications from around 2016. Over  the next two to three years, effective generic LED solutions  to replace incandescent lamps will arrive on the market,  although they will be somewhat pricey at first.
Keywords: Internet of things (IoT); Light Emitting Diodes (LED); Microcontroller; Node MCU; Processors